The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1002/ch.99
|View full text |Cite
|
Sign up to set email alerts
|

Response expectancies and beliefs about hypnosis: another look

Abstract: The present study found 266 undergraduates' pre‐induction beliefs about hypnosis and their self‐reported expectation of experiencing hypnosis to correlate with their performance on the Harvard Group Scale of Hypnotic Susceptibility, Form A (Shor & Orne, 1962). Futhermore, participants tended to label their hypnotic experience (on a 7‐point scale employed by Radtke and Spanos, 1982) in a manner consistent with their pre‐induction beliefs and expectancies. Finally, the present study showed that pre‐induction exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…No information was found on this topic, other than that most people think it requires relaxation. 39 A number of studies have addressed the question of control (n=5 22,28,38,40,41 ) within the transition into trance, these have found that the majority of people reject the ideas that the hypnotist is in charge 40 , and that people can be hypnotized against their will. 22,28 Most believe that collaboration is required for hypnosis.…”
Section: Hypnotizabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…No information was found on this topic, other than that most people think it requires relaxation. 39 A number of studies have addressed the question of control (n=5 22,28,38,40,41 ) within the transition into trance, these have found that the majority of people reject the ideas that the hypnotist is in charge 40 , and that people can be hypnotized against their will. 22,28 Most believe that collaboration is required for hypnosis.…”
Section: Hypnotizabilitymentioning
confidence: 99%
“…39 A number of studies have addressed the question of control (n=5 22,28,38,40,41 ) within the transition into trance, these have found that the majority of people reject the ideas that the hypnotist is in charge 40 , and that people can be hypnotized against their will. 22,28 Most believe that collaboration is required for hypnosis. 38,41 Of those papers which examined respondents' perception of their own, and other people's, hypnotizability (n=5), 22,28,[42][43][44] the majority reported that most people felt they could enter a hypnotic state.…”
Section: Hypnotizabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Social cognitive theorists contend that expectations play a preeminent role in responding to hypnotic suggestions (e.g., Kirsch & Lynn, 1995;Page, Handley, & Green, 1997). Kirsch, Silva, Comey, and Reed (1995), for example, determined that response expectancy, relative to measures of absorption, fantasy proneness, and motivation, was the strongest single predictor of hypnotic responsiveness.…”
mentioning
confidence: 98%
“…Kroger, 1963;Marcuse, 1964;Wallace, 1979;Crasilneck, 1985;Pratt, Wo od and Alman, 1988;Vingoe, 1995;Page, Handley and Green, 1997;Johnson and Hauk, 1999;Koizumi, 2001). According to Kroger (1963), the public's misperception and the concomitant fears cluster around the loss of control, for example, 'I will reveal secrets'; 'I will be made to do things against my will'; 'the hypnotist will have complete control of my mind'.…”
Section: Introductionmentioning
confidence: 99%